Strength Abilities: Assessment of Training Effects of Strength Loads in Boys Aged 8 Years - Sergii Iermakov; Olha Ivashchenko; Oleg Khudolii; Sergii Chernenko (OVS LLC, 2020)
The purpose of this paper is to determine the impact of strength training modes on the dynamics of training effects in 8-year-old boys.  Materials and methods. The study participants were 48 boys aged 8. The experiment was performed using a 22 factorial design. The study implemented the first variant of the combined method for developing arm and shoulder muscles (station І), strength of abdominal muscles (station ІІ), strength of back muscles (station ІІІ), and strength of leg muscles (station IV). The study materials were processed using the IBM SPSS 22 statistical analysis program. Discriminant analysis was performed. The study examined the impact of four variants of strength load on the immediate training effect (ITE1) after performing exercises at four stations, the immediate training effect (ITE2) after training, and the delayed training effect (DTE) 24 hours after training.  Results. The findings indicate that each of the variants of strength load can be effectively used depending on educational objectives of both one or a series of physical education lessons, and also show that the ITE and DTE of strength training depend on the initial level of fitness and the total amount of strength training in a physical education lesson.  Conclusions. The findings point to the possibility of using a discriminant function to assess and predict the development of strength in 8-year-old boys. The study confirmed the effectiveness of using factorial designs to obtain objective data on the dynamics of training effects in primary school pupils.